Distinct plasma cytokine and chemokine profiles in severe COVID-19 and septic shock - Se Ju Lee; Jaehoon Kim; Min Han; Jung Ah Lee; Yongseop Lee; Jung Ho Kim; Jin Young Ahn; Su Jin Jeong; Nam Su Ku; Joon-Sup Yeom; Jun Yong Choi (PLoS ONE, 2026)
Background Severe Coronavirus Disease 2019 (COVID-19) and septic shock are both characterized by dysregulated host immune responses. While similarities and differences in immune responses between COVID-19 and bacterial sepsis have been reported, direct comparative analyses remain limited. This study aims to characterize the immunologic status of patients with COVID-19 and sepsis through plasma cytokine/chemokine analysis, thereby providing additional candidates for immunomodulatory therapy for COVID-19. Methods We included patients diagnosed with severe COVID-19 or septic shock with lymphopenia, matched for age, sex, steroid administration, and severity. A total of 20 analytes were measured using Luminex assay. Results A total of 36 patients were enrolled. Plasma granulocyte-macrophage colony-stimulating factor (GM-CSF) concentrations were significantly higher in the COVID-19 group (5.3 pg/ml; IQR, 3.6–16.3 vs 0.0 pg/ml; IQR, 0.0–3.6; P = 0.010). Plasma interleukin-10 (IL-10) (0.0 pg/ml; IQR, 0.0–4.8 vs 28.8 pg/ml; IQR, 7.5–51.7; P = 0.003) and IL-15 (0.0 pg/ml; IQR, 0.0–0.0 vs 0.0 pg/ml; IQR, 0.0–5.6; P = 0.024) levels were significantly higher in the sepsis group. Firth logistic regression analysis showed that plasma IL-6, IL-8, and CXCL16 levels were associated with new organ support in the sepsis group, while IL-15, CXCL16, and IL-1RA levels tended to be associated in the COVID-19 group. Conclusion At day 7 after diagnosis, both groups exhibited active proinflammatory responses, but only the sepsis group showed prominent anti-inflammatory responses. The persistent elevation of GM-CSF in the COVID-19 group, even with steroid administration, highlights its potential as a therapeutic target and underscores the need for patient stratification in immunomodulatory trials.